Non-adherence to anti- diabetic therapy and its consequences among type-2 diabetic patients in a tertiary care hospital - J., Veeresh; Chavan, Vasanth R.; Arshad, Mohammad; M., Raghunandan; Fayazuddin, Mohd. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Despite the extensive therapy options available for various stages of type 2 diabetes, studies have indicated that less than 50% of patients achieve the glycemic goals. Failure to attain the desired therapeutic goal might be related to inadequate adherence. Objectives of present study were to determine the extent of non-adherence to antidiabetic medications and identify reasons for the same. Methods: A cross-sectional, observational, questionnaire-based study was conducted to assess the level of non-adherence to antidiabetic therapy among type 2 diabetics attending medicine outpatient department or admitted to the wards of a tertiary care hospital from Jan 2015 to Jan 2016. A pretested and validated questionnaire was used to assess the level of adherence. Reasons for missing medications were also elicited. Data thus collected was analysed using a suitable statistical software. Results: Out of the 210 study participants, 55.2% were females. Most participants were in the age group of 51-60. The mean duration of diabetes was 8.17± 5.39. The most common diabetes-related complication was Diabetic Keto Acidosis (DKA), followed by diabetic foot ulcer. The average number of drugs per prescription was 1.98 ± 1.05. Poor glycemic control was observed in 58% and non-adherence to treatment in 45.2% of study participants. Conclusions: Good adherence to antidiabetic therapy is fundamental for good glycemic control which in turn prevents the occurrence of short and long-term complications of diabetes. Poor doctor-patient intercommunication and inadequacy on part of physicians to adjust medications negatively affect adherence. Active participation of the patient is also equally important.